Sleep Quality and Nutritional Status Among Indonesian Children and Adolescents: A Systematic Review - Ulil Albab Habibah; Fanny Anggiastuti Fatima; Herwinasla Purnanabila; Windyan Kestri Herdhani; Satria Akbar Putra Asmara (Epidemiology and Society Health Review (ESHR), 2026)
Background: Nutritional status is the result of an individual’s nutrient intake and requirements. In Indonesia, issues related to children’s nutritional status remain a major problem. The relationship between these two variables is mediated by two important hormones involved in appetite regulation: leptin and ghrelin. In a cohort study, results showed a relationship between leptin levels and sleep quality. Although global studies have demonstrated a relationship between these two variables, studies in Indonesia have yielded mixed results. Therefore, this systematic review aims to systematically synthesize the evidence regarding the relationship between sleep quality and nutritional status in children in Indonesia. Method: This literature review was conducted in March 2026. The databases used for the literature review were Google Scholar, PubMed, ScienceDirect, and Garuda, with periode 2021-2026 publication year. The search strategy used the keywords: ("sleep quality") AND ("nutritional status") AND ("children") AND ("Indonesia"), including equivalent Indonesian terms. Article selection was conducted in accordance with the PRISMA guidelines. Results: Eleven studies were included in the literature review. The sample size for each study ranged from 52 to 221 participants. Eight studies showed a significant association between sleep quality and nutritional status, while three studies showed no significant association. Conclusion: The findings of this review confirm that sleep quality is not the sole factor determining nutritional status. Therefore, intervention efforts to improve the nutritional status of children and adolescents must be comprehensive, focusing not only on improving sleep quality but also on improving dietary habits, increasing physical activity, and regulating social media use.